Utility of Plasma Microbial Cell-Free DNA Decay Kinetics After Aortic Valve Replacement for Bartonella Endocarditis: Case Report - Solanky, Dipesh; Ahmed, Asim A.; Fierer, Joshua; Golts, Eugene; Jones, Meghan; Mehta, Sanjay R. (Frontiers in Tropical Diseases, 2022)
Background Detection and sequencing of circulating microbial cell-free DNA (mcfDNA) in plasma is an increasingly popular tool for diagnosing many infectious diseases, but could also be used to monitor the progress of infection. However, the decay of this microbial cell-free DNA in blood following treatment has not been previously characterized. Case Presentation A 53 year-old male was diagnosed with Bartonella quintana bioprosthetic aortic valve endocarditis by sequencing of the mcfDNA in the blood (Karius, Redwood City, CA). We then monitored the kinetics of decay of mcfDNA after parenteral antibiotics and valve resection in this individual. We measured plasma mcfDNA (Karius) in serial samples obtained in the operating room to calculate mcfDNA half-life after valve resection. After four weeks of parenteral antibiotics, Bartonella mcfDNA signal decreased by 78%. The signal subsequently rose during operative manipulation of the infected valve but dropped 81-fold over four hours following valve resection. The half-life of mcfDNA between the time shortly following resection of the infected valve and 24 to 48 hours post-operatively was between 35 and 115 minutes. The trend in mcfDNA signal was characterized by rapid and then slower phases of decay within 24 hours, and little change between 24 and 48 hours. Conclusions This study is one of the first to characterize decay kinetics of mcfDNA and highlights the potential of monitoring mcfDNA in addressing major challenges in infective endocarditis management, including monitoring the response to therapy, and as an early screen for recurrence.